2021
DOI: 10.3389/fonc.2021.734853
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram Improves the Anti-PD-1 Therapy Efficacy by Regulating PD-L1 Expression via Epigenetically Reactivation of IRF7 in Triple Negative Breast Cancer

Abstract: Immune checkpoint blockade (ICB), particularly programmed death 1 (PD-1) and its ligand (PD-L1), has shown considerable clinical benefits in patients with various cancers. Many studies show that PD-L1 expression may be biomarkers to help select responders for anti-PD-1 treatment. Therefore, it is necessary to elucidate the molecular mechanisms that control PD-L1 expression. As a potential chemosensitizer and anticancer drug, disulfiram (DSF) kills tumor cells via regulating multiple signaling pathways and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Probably, the generation of Cu(DETC) 2 might reduce the expression and activity of DNA methyltransferase 1 (DNMT1), leading to the epigenetic reactivation of interferon regulatory factor 7 (IRF7) and subsequent PD‐L1 upregulation through the axis of DNMT1/IRF7/PD‐L1. [ 30 ] Moreover, we also investigated the capacity of CuCH‐NCs/DSF combination to induce immunogenic cell death (ICD) effect for augmenting antitumor immune response. [ 31 ] Clearly, the 2.5‐fold increase of calreticulin (CRT) on the cell surface, 3.8‐fold decrease of intranuclear high mobility group protein B1 (HMGB1), and 2.2‐fold increase of extracellular ATP level were respectively observed in the 4T1 cells upon treatment with CuCH‐NCs/DSF combination (Figure 7A,B).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Probably, the generation of Cu(DETC) 2 might reduce the expression and activity of DNA methyltransferase 1 (DNMT1), leading to the epigenetic reactivation of interferon regulatory factor 7 (IRF7) and subsequent PD‐L1 upregulation through the axis of DNMT1/IRF7/PD‐L1. [ 30 ] Moreover, we also investigated the capacity of CuCH‐NCs/DSF combination to induce immunogenic cell death (ICD) effect for augmenting antitumor immune response. [ 31 ] Clearly, the 2.5‐fold increase of calreticulin (CRT) on the cell surface, 3.8‐fold decrease of intranuclear high mobility group protein B1 (HMGB1), and 2.2‐fold increase of extracellular ATP level were respectively observed in the 4T1 cells upon treatment with CuCH‐NCs/DSF combination (Figure 7A,B).…”
Section: Results and Discussionmentioning
confidence: 99%
“…17 Recent clinical studies have revealed that DSF can effectively treat many types of cancer, including lung cancer, 18 melanoma, 19 glioblastoma, 20 and triple-negative breast cancer. 21 The anticancer activity of DSF has been reported to be Cu 2+ dependent, because DSF rapidly metabolizes in vivo to diethyldithiocarbamate (DTC), and DTC chelates rapidly with Cu 2+ to produce a DTC–copper complex (CuET), which are key active ingredients in the anticancer process. 17,22 Various anticancer mechanisms of CuET have been reported, including disrupting the p97-NPL4-UFD1 pathway, inhibiting the ubiquitin–proteasome system and inducing oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In a wide range of preclinical studies disulfiram has demonstrated broad anticancer activity across tumor types. 3,[6][7][8][9] Glioblastoma (GB) is the most common and unfortunately also the most malignant of the diffuse gliomas. 10,11 No major breakthrough in systemic treatment has occurred since the introduction of temozolomide.…”
Section: Introductionmentioning
confidence: 99%
“…It is in this context that disulfiram, a drug used to treat alcohol dependency since 1947, has gained increased attention as a potential anticancer drug . In a wide range of preclinical studies disulfiram has demonstrated broad anticancer activity across tumor types …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation